Optimizing the Potential of MSMEs Through an Integrated Strategy: Financial Information Recording Application System (SIAPIK), Social Media Marketing, and Halal Certification - Aziz, Nur Jannah Abdi; Jatnika, Muhammad Dzulfaqori; Maryani, Sri (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT MSMEs play an important role in the local economy, but often face obstacles in financial management, marketing, and product legality. To overcome this, this service program was implemented with a focus on empowering MSMEs in Sukaratu Village through an integrated strategy. The training and mentoring provided covers three main areas: (1) financial recording with the SIAPIK application, (2) digital marketing using social media such as Instagram, and (3) halal certification assistance to improve product legality. The program also includes the creation of a website to monitor the development of MSMEs online. As a result of the activities, MSMEs showed improvements in the ability to record finances and make reports accurately, utilize social media for wider marketing, and prepare for halal certification. Constraints such as limited initial knowledge and infrastructure were overcome through intensive training and direct mentoring. The program also produced outputs in the form of scientific publications, training modules, and a web-based monitoring system to ensure program sustainability. Through this program, MSMEs are better prepared to face market challenges and have a stronger foundation to develop sustainably. Keywords: MSMEs, Financial Reporting, SIAPIK, Halal Certification, Social Media Marketing